Respuesta :

Step-by-step explanation:

Hey, there!

Here,

[tex] = 4 {x}^{2} - 4x + 1[/tex]

[tex]or ,\: ( {2x)}^{2} - 2.2x .1 + 1[/tex]

[tex]or ,\: ( {2x - 1)}^{2} [/tex]

We got this because,

[tex]( {2x - y)}^{2} = 4 {x}^{2} - 4x + 1[/tex]

By using formula,

[tex]( {x - y)}^{2} = {x}^{2} - 2xy + 1[/tex]

Hope it helps..

Answer: (x+-0.5)²=0

Step-by-step explanation:

4x²-4x+1=0

(2x-1)²=0 ⇔ completing the square

--------------------------------------------

since the question asked for the x should be 1, then we should divide 2x by 2 so to get rid of the 2 in front of the x.

this will change the original equation into: (x+(-0.5))²=0

------------------------------------------------------------------------------------------------------------

You can also directly divide 4 from 4x²-4x+1=0 to get rid off the terms in front of x.

x²-x+0.25=0

(x-0.5)²=0

(x+(-0.5))²=0